Islamic Financial Literacy and Its Effects on Intention to Use Islamic Bank - Sariyatul Ilyana; Fitra Prasapawidya Purna; Dian Friantoro (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2021)
Introduction: Islamic finance in Indonesia has a rapid development in this millennial era. Islamic bank is starting to become an option. Islamic financial literacy has an important role for peoples, not least by students. Student as young generation will have a long future and must have the ability of financial skills. If someone takes a decision wrongly then it will result in a lack of retirement planning and poor borrowing behavior. Purpose/Objective Study: The aim of this study focuses on measuring the level of Islamic financial literacy, exploring the effects of the hopelessness, religiosity and financial satisfaction on Islamic financial literacy, and determining the effects of Islamic financial literacy on intentions to use Islamic banks among students. Design/Methodology/Approach: The models being used are simple and multiple regression with ordinary least square method. 376 students samples are taken from Islamic universities in Yogyakarta. Findings: The results proved that students have a high Islamic financial literacy, hopelessness has a negative and insignificant effect while religiosity and financial satisfaction have positive and significant effect toward Islamic financial literacy. The whole model has significant effect toward Islamic financial literacy. This study proved that Islamic financial literacy has a positive and significant effect on the intention to use Islamic bank. Article Type : Research Paper